The complete chloroplast genome of Swertia cordata - Huang, Li (Mitochondrial DNA B Resour, 2019)
Swertia cordata, a herbaceous plant, has been used in medicines as an alternative febrifuge and anthelmintic. In this study, the complete chloroplast DNA sequence of S. cordata was assembled. It is 153,429 bp in length, including a large single-copy region of 83,613 bp and a small single-copy region of 18,038 bp separated by a pair of inverted repeat regions of 25,889 bp each. A total of 129 genes are detected, including 84 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The complete chloroplast genome of S. cordata will help to study the genetic diversity and phylogenetic analysis of Swertia.